Influenza enhances host susceptibility to non-pulmonary invasive Streptococcus pyogenes infections - Andrea L. Herrera; Rashaun Potts; Victor C. Huber; Michael S. Chaussee (Virulence, 2023)
Streptococcus pyogenes (group A streptococcus; GAS) causes a variety of invasive diseases (iGAS) such as bacteremia, toxic shock syndrome, and pneumonia, which are associated with high mortality despite the susceptibility of the bacteria to penicillin ex vivo. Epidemiologic studies indicate that respiratory influenza virus infection is associated with an increase in the frequency of iGAS diseases, including those not directly involving the lung. We modified a murine model of influenza A (IAV)-GAS superinfection to determine if viral pneumonia increased the susceptibility of mice subsequently infected with GAS in the peritoneum. The results showed that respiratory IAV infection increased the morbidity (weight loss) of mice infected intraperitoneally (i.p.) with GAS 3, 5, and 10 d after the initial viral infection. Mortality was also significantly increased when mice were infected with GAS 3 and 5 d after pulmonary IAV infection. Increased mortality among mice infected with virus 5 d prior to bacterial infection correlated with increased dissemination of GAS from the peritoneum to the blood, spleen, and lungs. The interval was also associated with a significant increase in the pro-inflammatory cytokines IFN-γ, IL-12, TNF-α, MCP-1 and IL-27 in sera. We conclude, using a murine model, that respiratory influenza virus infection increases the likelihood and severity of systemic iGAS disease, even when GAS infection does not originate in the respiratory tract.